PENINGKATAN KOMPETENSI PROFESIONAL GURU SD/MI MELALUI MENULIS DI MEDIA - Hamidulloh Ibda (Universitas Islam Nahdlatul Ulama Jepara, 2017)
Writing a scientific article is a necessity of elementary school teachers ormadrasah ibtidaiyah. In addition to reviving the scientific culture, writingbecomes a vehicle to hone the intellectual quality. By writing, teachers aremore diligent in reading, researching, analyzing and putting their ideas into perspective. Today there is plenty of space in the mass media to write, both popular scientific articles, essays, features and more. Writing becomes one component of improving quality and professional competence. Teachers are not only required to meet the competence of pedagogy, personality and social. Teachers' duties not only design and teach, but also the publication of scientific papers in the mass media. Writing in the mass media is very different from in journals and books, because writing should be popular, actual and solutive. In improving professional competence, teachers are required to fulfill Sustainable Culture Development in accordance with the Regulation of State Minister of State Apparatus Empowerment and Bureaucracy Reform No. 16 of 2009 on Teacher Functional Position and Credit Score. Sustainable Culture Development is the main element whose activities are given credit numbers for teacher career development, in addition to the other two main elements. Permenpan RB number 16 of 2009 divides Sustainable Culture Development consists of 3 components including self-development, scientific publications and innovative works. Professional teacher competence can be achieved by fulfilling Sustainable Culture Development by writing in mass media. If achieved, then become an instrument to improve the professional competence of teachers. Menulis artikel ilmiah merupakan keniscayaan guru Sekolah Dasar (SD) atau Madrasah Ibtidaiyah (MI). Selain menghidupkan budaya ilmiah, menulis menjadi wahana mengasah kualitas intelektual. Dengan menulis, guru semakin rajin membaca, meneliti, menganalisis dan menuangkan gagasannya. Saat ini banyak ruang di media massa untuk menulis, baik artikel ilmiah populer, esai, feature dan lainnya. Menulis menjadi salah satu komponen meningkatkan kualitas dan kompetensi profesional. Guru tidak sekadar dituntut memenuhi kompetensi pedagogi, kepribadian dan sosial. Tugas guru tidak hanya merancang dan mengajar, namun juga publikasi karya ilmiah di media massa. Menulis di media massa sangat berbeda dengan di jurnal dan buku, karena tulisan harus populer, aktual dan solutif. Dalam meningkatkan kompetensi profesional, guru dituntut memenuhi Pengembangan Keprofesian Berkelanjutan (PKB) sesuai dengan Peraturan Menteri Negara Pemberdayaan Aparatur Negara dan Reformasi Birokrasi Nomor 16 Tahun 2009 tentang Jabatan Fungsional Guru dan Angka Kreditnya. PKB merupakan unsur utama yang kegiatannya diberikan angka kredit untuk pengembangan karir guru, selain kedua unsur utama lainnya. Permenpan RB Nomor 16 Tahun 2009 membagi PKB terdiri atas 3 komponen meliputi pengembangan diri, publikasi ilmiah dan karya inovatif. Kompetensi profesional guru bisa dicapai dengan memenuhi PKB dengan cara menulis di media massa. Jika tercapai, maka menjadi instrumen meningkatkan kompetensi profesional guru.